2020
DOI: 10.1177/0312896220914383
|View full text |Cite
|
Sign up to set email alerts
|

Online or offline? Coaching media as mediator of the relationship between coaching style and employee work-related outcomes

Abstract: This article examines how leaders make use of different coaching media, namely face-to-face coaching and e-coaching, to coach and regulate the behavior and performance of followers. Specifically, we examine coaching medium as the mediator of the relationship between two coaching styles and three work outcomes (adaptive performance, creativity, and emotional exhaustion), based on a two-wave longitudinal field study of 114 employees in Hong Kong. The results of structural equation modeling show that the two coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The well-known book Sport and Physical Education in China provides an introduction to several subjects, including how sport has evolved in both ancient and contemporary China, how it is taught in schools and universities, how professionals train, how the Olympics work, and how sports science and medicine are all addressed are reported by Hui et al (5) and Gargo (6). Chinese undergraduate physical education aims to improve students' physical stamina and talents via thorough exercises that look at how the curriculum is set up in China from the instructors' perspective.…”
Section: Figure 1: Psychological Contract Violationmentioning
confidence: 99%
“…The well-known book Sport and Physical Education in China provides an introduction to several subjects, including how sport has evolved in both ancient and contemporary China, how it is taught in schools and universities, how professionals train, how the Olympics work, and how sports science and medicine are all addressed are reported by Hui et al (5) and Gargo (6). Chinese undergraduate physical education aims to improve students' physical stamina and talents via thorough exercises that look at how the curriculum is set up in China from the instructors' perspective.…”
Section: Figure 1: Psychological Contract Violationmentioning
confidence: 99%
“…For a long time, instructors have customarily used the telephone medium with trainees (Bagshaw & Bagshaw, 2002;Boyce & Clutterbuck, 2010;Bruck, Robinson, & Gallagher, 2021;Hui, Law, & Lau, 2021;Olszewski-Kubilius, 2013;Sailer, Schultz-Pernice, & Fischer, 2021). However, now the use of cyber-mediated techs is helping boost, extend, and substitute face-to-face training while transforming the overall training experience.…”
Section: What Is E-coaching and What Is The Motivation Behind E-coach...mentioning
confidence: 99%
“…Grant and Zackon (2004)'s research discovered that almost 64% of the study participants reported they used electronic methods of training at some point in time (Bucur, 2018). The data also revealed that 63% of trainers use their smartphones compared to 34% who prefer face-to-face meetings as the main way of Peyton Investments offer managerial training via phone, face-to-face email or direct messaging (Bagshaw & Bagshaw, 2002;Boyce & Clutterbuck, 2010;Bruck et al, 2021;Hui et al, 2021;Olszewski-Kubilius, 2013;Sailer et al, 2021).…”
Section: What Is E-coaching and What Is The Motivation Behind E-coach...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hammack-Brown's (2018) research offers some important insights regarding measurement invariance of managerial coaching behavior in traditional and virtual contexts. Recent research by Hui et al (2020) examining coaching types (guidance and facilitation) and coaching media (face-to-face and e-coaching through mobile instant messaging) found a positive relationship between facilitation coaching and e-coaching. However, considerably more research needs to be undertaken with regard to virtual and ecoaching by managers drawing upon organizations that are committed to coaching, and those who wish to build LOs where managerial and leader coaching likely play a central role.…”
Section: Managerial Coaching In the Context Of Learning Organizationsa Research Agendamentioning
confidence: 99%